Identifying Bixa orellana L. New Carotenoid Cleavage Dioxygenases 1 and 4 Potentially Involved in Bixin Biosynthesis - Us-Camas, Rosa; Aguilar-Espinosa, Margarita; Rodríguez-Campos, Jacobo; Vallejo-Cardona, Alba Adriana; Carballo-Uicab, Víctor Manuel; Serrano-Posada, Hugo; Rivera-Madrid, Renata (Frontiers in Plant Science, 2022)
Carotene cleavage dioxygenases (CCDs) are a large family of Fe2+ dependent enzymes responsible for the production of a wide variety of apocarotenoids, such as bixin. Among the natural apocarotenoids, bixin is second in economic importance. It has a red-orange color and is produced mainly in the seeds of B. orellana. The biosynthesis of bixin aldehyde from the oxidative cleavage of lycopene at 5,6/5’,6’ bonds by a CCD is considered the first step of bixin biosynthesis. Eight BoCCD (BoCCD1-1, BoCCD1-3, BoCCD1-4, CCD4-1, BoCCD4-2, BoCCD4-3 and BoCCD4-4) genes potentially involved in the first step of B. orellana bixin biosynthesis have been identified. However, the cleavage activity upon lycopene to produce bixin aldehyde has only been demonstrated for BoCCD1-1 and BoCCD4-3. Using in vivo (Escherichia coli) and in vitro approaches, we determined that the other identified BoCCDs enzymes (BoCCD1-3, BoCCD1-4, BoCCD4-1, BoCCD4-2, and BoCCD4-4) also participate in the biosynthesis of bixin aldehyde from lycopene. The LC-ESI-QTOF-MS/MS analysis showed a peak corresponding to bixin aldehyde (m/z 349.1) in pACCRT-EIB E. coli cells that express the BoCCD1 and BoCCD4 proteins, which was confirmed by in vitro enzymatic assay. Interestingly, in the in vivo assay of BoCCD1-4, BoCCD4-1, BoCCD4-2, and BoCCD4-4, bixin aldehyde was oxidized to norbixin (m/z 380.2), the second product of the bixin biosynthesis pathway. In silico analysis also showed that BoCCD1 and BoCCD4 proteins encode functional dioxygenases that can use lycopene as substrate. The production of bixin aldehyde and norbixin was corroborated based on their ion fragmentation pattern, as well as by Fourier transform infrared (FTIR) spectroscopy. This work made it possible to clarify at the same time the first and second steps of the bixin biosynthesis pathway that had not been evaluated for a long time.